The Influence of Gadget Use Intensity on Reading Comprehension Skills of Fourth Grade Elementary School Students - Sevian Ageng Wahono; Nurul Istiq'faroh (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
The development of digital technology has increased the intensity of gadget use among elementary school students, potentially affecting their reading literacy skills. This study aims to analyze the effect of gadget use intensity on reading comprehension skills in the material of determining the main idea of ​​fourth-grade students of SDN Lidah Wetan II Surabaya. The study used a quantitative approach with a causal associative design. The research sample consisted of 27 fourth-grade C students selected through a purposive sampling technique, while the instrument trial involved 25 fourth-grade B students. Data collection was carried out using a gadget use intensity questionnaire and a reading comprehension ability test. Data were analyzed through validity, reliability, normality, linearity, Pearson correlation, and simple linear regression tests. The results showed that gadget use intensity had a negative and significant relationship with reading comprehension ability (r = -0.518; p = 0.006). The regression analysis produced a coefficient of determination (R²) of 0.268, indicating that gadget use intensity contributed 26.8% to reading comprehension ability, while 73.2% was influenced by other factors. These findings indicate that the higher the intensity of gadget use, the lower students’ ability to identify the main idea of ​​a reading. Therefore, monitoring and educational use of gadgets are necessary to support the development of students’ reading literacy.